Animation of crack propagation by means of an extended multi-body solver for the material point method. (December 2017) - Wretborn, Joel; Armiento, Rickard; Museth, Ken
Highlights: New N-body collision algorithm for the material point method framework. Dynamic crack propagation algorithm using multi-body solver and particle constraints. Example contact and tearing scenarios are provided as results. Graphical abstract: Abstract: We propose a multi-body solver that extends the Material Point Method (MPM) to simulate cracks in computer animation. We define cracks as the intersection between pieces of bodies created by a pre-fracture process and held together by massless particle constraints (glue particles). These pieces are simulated using a MPM multi-body solver extended by us to efficiently handle N -body collisions. Benefits of the present work include (1) low computational overhead compared to a normal MPM algorithm; (2) good scaling in three dimensions due to our use of sparse grids for background computations; (3) allowing for an easy and controllable setup phase to simulate a desired material failure mode, which is especially useful for computer animation.